The Effect of Traditional Market Revitalization in Wonoayu People's Market, Sidoarjo Regency - Nur Rosidah Hayati; Isna Fitria Agustina (Universitas Muhammadiyah Sidoarjo, 2022)
The government in this case is trying to improve the regional economy, one of which is in traditional markets by carrying out a traditional market revitalization program with the aim of improving traditional market facilities and infrastructure which has recently experienced a decline. The purpose of this research is to find out and understand more about the effect of revitalizing traditional markets in the Wonoayu People's Market, Sidoarjo Regency. This research focuses on one theory of revitalization, namely Physical Intervention, Economic Rehabilitation and Social Revitalization. The method used in this study is a qualitative method with data collection techniques carried out by documentation, interviews and using sources from books, journals and policy documents. Keywords: Policy Influence, Traditional Markets, Revitalization.